Green computing: an environmental sensitivity offer (Gaceta Técnica, 2015)
This article describe an environmental sensitivity offer for the students of Systems 1 course of the Computer Engineering Program of Universidad Centroccidental Lisandro Alvarado (UCLA), based on the green computing practice. The offer seeks to sensitize to these professional futures, in order that they could help to improve the environmental situation of the planet. The study began with the review of the foundations of the green computing, supported on the monographic documentary investigation, then were selected the green computing practices for including in the offer, the offer was designed, was implemented and finally, based on the field investigation and across the application of a structured interview and the use of a check list, was measured up and analyzed the results. The offer consisted of adding new instructions to the practical work of the course, orientated to using the Information and Communication Technologies (ICT) to minimize the energetic consumption and to generate ICT solutions that reduce the energetic consumption. The practices mainly accepted went related to the ICT use to minimize the energetic consumption, specifically, the use optimizing of printers, ink and paper
Keywords: environmental sensitivity; green computing; TIC